Nivel de Competencias Digitales de los estudiantes de la Facultad de Ciencias de la Educación, Humanas y Tecnologías - Vela Barragán, Marlon Fabricio (2023)
The role of digital skills is fundamental in the entire training process and in particular, of future teachers; however, at the Faculty of Education, Human Sciences and Technology level, it has yet to be discovered at what level the students are at the end of their careers. For this reason, this study aimed to determine the level of digital skills of the students of the Faculty in question. The research had a quantitative approach, non-experimental design, type and descriptive level. The survey technique was obtained with an online questionnaire adapted from the "DigComp" 2.0 model, which was applied to 192 eighth-semester students from 11 Faculty careers, concluding that approximately 1% of the participants are in a null level, 41% at a basic level, 49% at an intermediate level and 9% at an advanced level. The highest level was intermediate and the careers in which more than 50% of their students showed this level were: Graphic Design, Pedagogy of History and Social Sciences, Pedagogy of Experimental Sciences, Mathematics and Physics, and Pedagogy of Experimental Computer Sciences. It is recommended that, according to the results obtained, each career prepare training to reinforce the areas with lower levels of digital skills.